Milled pavement texturing to optimize skid improvements. (30th December 2015) - Gao, Lu; de Fortier Smit, André; Prozzi, Jorge A.; Buddhavarapu, Prasad; Murphy, Mike; Song, Lingguang
Highlights: Pavement texturing can improve flexible pavement's skid resistance. A forward speed of 70–80 feet per minute is recommended. A cutting depth between 0.25 and 0.5 inches are recommended. Abstract: This research evaluated the use of a milling machine to texture pavement surfaces and its effect on skid improvement. Texturing tests with different milling drums, forward speeds and cutting depths were conducted on 31 asphalt pavement sections across Texas. Macrotexture and friction were measured before the milling and 3, 6, 12, and 18 months after the milling. The results show that sections milled with fine drums exhibited a higher skid resistance and macrotexture after milling. The test results also indicate that the forward milling speed is positively associated with both skid resistance and macrotexture. In other words, higher milling speeds tend to produce surfaces with higher skid resistance and macrotexture. The data suggests that milling operations on average provide a service life of about 12 months on seal coats, whereas milling on HMA sections extends the service life beyond 18 months.